Action, instant and aspectuality of visual representation: narrative and visual discourse in photojournalism - Picado, Benjamim (2009)
This text intends to seek the relation between Structuralism in textual analysis and some approaches of contemporary aesthetic theories on the issue of the interpretation of visual representations: we focus on the problem of the meaning of the instant, as a cardinal point of the ways by which photographic images report themselves to actions; in these terms, we take the problem of the photographic instant as simultaneously expressing the arrest of action’s temporal integrity and as a proper narrative function. We are especially interested in the evaluation of the connections between representational regimes and perceptual structures, in the very same way Umberto Eco approaches the remissions between iconography and perceptual codes; the notion of “aspectuality”, introduced here by contemporary aesthetic theories, seems to be a central item in order to enable the exploration of the relation between images and perception.